Kant and Mendelssohn about Idealism - Sá Pereira, Roberto Horácio (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This paper aims to reconstruct Kant’s Refutation of Idealism as a successful world-directed transcendental argument against Mendelssohn’s “problematic idealism.” Mendelssohn’s problematic idealism arises from both a metaphysical and an epistemological doctrine that has an undeniable Cartesian root. Metaphysically, he assumes what we may call a “commonsense realist” view: that appearances outside our mind in space are, in themselves, material in nature, just as appearances within our mind are, in themselves, mental in nature (a position he refers to as “dualism”). Epistemologically, Mendelssohn holds that there is a fundamental hiatus between the material and mental worlds since the inference from our internal representations to the purported external material things they supposedly copy is, at best, problematic—this is what we refer to as “indirect realism.” Kant’s Refutation challenges both aspects of this view. On the epistemological level, Kant argues that we have direct awareness of the existence of external material things in space. On the metaphysical level, he claims that the ultimate nature of external things is neither material nor mental but consists instead of mind-independent things-in-themselves—noumena in the negative sense. However, Kant’s argument can only succeed as a world-directed transcendental argument if it is able to establish the truth of a persistent mind-independent thing in itself is a necessary condition for the conscious of our existence determined in time.